Crop coefficient of a popular potato variety in Bangladesh (Bangladesh Journal of Agricultural Research, 2017)
Crop evapotranspiration (ETc) and crop coefficient (Kc) values of potato (variety: BARI Alu -7, Diamant) at different growth stages were determined through lysimeter method at Irrigation and Water Management Division of Bangladesh Agricultural Research Institute (BARI), Gazipur during 2008 - 2009. The study was conducted by applying irrigation at 25 and 40 days after planting (DAP) allowing drainage (AD) (T1), at 25, 40, and 55 DAP AD (T2), at 25, 40, and 60 DAP AD (T3), and at 25, 40, 55, and 60 DAP AD (T4) within and adjacent of four lysimeter tanks. Irrigation at 25, 40, and 55 DAP produced the highest tuber yield and was considered to be suitable for estimating seasonal ETc, and Kc values. The seasonal highest ETc was found to be 162 mm. The Kc values of 0.25, 0.62, 0.70 and 0.18 were determined at initial, development, midseason and late season stages of potato. These values differed slightly from the FAO recommended values. As the lysimeter provides control environment, the Kc values determined by this method are most dependable and recommended for estimating ETc of potato in semi-arid climatic conditions of Bangladesh.Bangladesh J. Agril. Res. 42(1): 67-76, March 2017